2019
DOI: 10.30552/ejihpe.v9i3.332
|View full text |Cite
|
Sign up to set email alerts
|

Resilience as a protective factor of chronic stress in teachers

Abstract: The Neuroscience considers that the most resilient people maintain greater emotional balance in stress situations, which allows them to better withstand the pressure and, consequently, to experience a greater sense of control and ability to cope with difficult situations. The aim of the cross-sectional study is to analyze the preventive effect of resilience on burnout perceived by Secondary E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 20 publications
0
9
0
6
Order By: Relevance
“…Several studies have demonstrated a positive relationship between teachers' well-being and their efficacy in teaching [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, practical and applied research on training programs to improve teacher well-being and efficacy is still needed, particularly in light of the extreme challenges posed by the COVID-19 crisis.…”
Section: Work-related Stress Among Teachersmentioning
confidence: 99%
“…Several studies have demonstrated a positive relationship between teachers' well-being and their efficacy in teaching [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, practical and applied research on training programs to improve teacher well-being and efficacy is still needed, particularly in light of the extreme challenges posed by the COVID-19 crisis.…”
Section: Work-related Stress Among Teachersmentioning
confidence: 99%
“…However, teachers must be resilient to overcome these circumstances and learn to deal adversity in the current educational systems [7]. In situations of adversity at work, de Vera-García and Gabari-Gambarte [8] mention that the most resilient teachers achieve better skills and competencies in work commitment and reduce chronic stress; while, the less resilient teachers have a predisposition to increase the effect of tiredness and indifference. Furthermore, resilience has been shown to help reduce perceived stress and feelings of exhaustion in teachers [9].…”
Section: Introductionmentioning
confidence: 99%
“…For H.2, no negative relationships are observed between all the variables that make up the subscales of resilience and burnout syndrome. Very distant results were obtained by de Vera and Gambarte (2019), stating de Vera-García and Gabari-Gambarte, (2019) that resilience is a protective factor against disruptive states such as burnout syndrome and stress. In this case, the study by Martínez-Ramón et al (2021) states that, in the presence of adverse situations, teachers with higher levels of resilience do not burn out, but acquire a greater work commitment, overcoming difficulties.…”
Section: Discussionmentioning
confidence: 96%